What Gives Me Hope - Leslie, Heather (Maine Policy Review, 2023)
The commentary focuses on the author’s experiences over the last several years in Maine where she has conducted research, mentored students, and collaboratde with diverse community partners on a number of projects focused on shellfish fisheries co-management and other community-led resilience projects in coastal Maine.